Greenland, view of Kjerulf Fjord through to Dicksons Fjord - Boyd, Louise Arner, 1887-1972 (1931)
August 2, 1931. Kjerulfs [Kjerulf] Fjord. Through to Dickson [Dicksons] Fjord. In background; L.A.B.'s Curry-comb Peak, forming west side of Left Valley. On side of mountain are piles of earth like mine-dumps or volcanic cones: See photos 26-H-1 & 24-F-7. In foreground; stream descending Left Valley. Photo taken looking west from east side of Left Valley.